Using artificial intelligence systems for intensive safe cultivation of crops-short communication - Mikhailov, D.; Fedorov, V.; Mitrokhin, M.; Pronichkin, A. K.; Soytong, K. (My University, 2021)
The modern artificial intelligence systems for intensive safe cultivation of crops is proposed. Predicted crop is based on platforms of vitisFlower, vitisBerry and FruitSize). The expert assesses economic and environmental impacts for profitability of agro-industrial production. Results are significantly increased in the sustainability of the company to reduce the production costs, obtained an environmentally friendly product. Artificial intelligence systems are created a tool for a simplified of precision farming systems in small companies with the ability to access the platform. The project can be focused to develop and distribute the precision farming systems that supports companies' decisions about the risk of actual production and disease prediction models. The result should be corresponded to decrease the production inputs, and created the low cost hardware / software "data package" within the full cycle of agro-industrial production.
Keywords: Agro-industrial production; Artificial intelligence systems; Farming systems; Safe cultivation of crops